Grip strength is inversely associated with DNA methylation age acceleration. Issue 1 (9th November 2022) - Peterson, Mark D.; Collins, Stacey; Meier, Helen C.S.; Brahmsteadt, Alexander; Faul, Jessica D.
Abstract: Background: There is a large body of evidence linking muscular weakness, as determined by low grip strength, to a host of negative ageing‐related health outcomes. Given these links, grip strength has been labelled a 'biomarker of aging'; and yet, the pathways connecting grip strength to negative health consequences are unclear. The objective of this study was to determine whether grip strength was associated with measures of DNA methylation (DNAm) age acceleration. Methods: Middle age and older adults from the 2006 to 2008 waves of the Health and Retirement Study with 8–10 years of follow‐up were included. Cross‐sectional and longitudinal regression modelling was performed to examine the association between normalized grip strength (NGS) and three measures of DNAm age acceleration, adjusting for cell composition, sociodemographic variables and smoking. Longitudinal modelling was also completed to examine the association between change in absolute grip strength and DNAm age acceleration. The three DNAm clocks used for estimating age acceleration include the established DunedinPoAm, PhenoAge and GrimAge clocks. Results: There was a robust and independent cross‐sectional association between NGS and DNAm age acceleration for men using the DunedinPoAm (β: −0.36; P < 0.001), PhenoAge (β: −8.27; P = 0.01) and GrimAge (β: −4.56; P = 0.01) clocks and for women using the DunedinPoAm (β: −0.36; P < 0.001) and GrimAge (β: −4.46; P = 0.01) clocks. There was also an independent longitudinal association between baseline NGS and DNAm age acceleration for men (β: −0.26; P < 0.001) and women (β: −0.36; P < 0.001) using the DunedinPoAm clock and for women only using the PhenoAge (β: −8.20; P < 0.001) and GrimAge (β: −5.91; P < 0.001) clocks. Longitudinal modelling revealed a robust association between change in grip strength from wave 1 to wave 3 was independently associated with PhenoAgeAA (β: −0.13; 95% CI: −0.23, −0.03) and GrimAgeAA (β: −0.07; 95% CI: −0.14, −0.01) in men only (both P < 0.05). Conclusions: Our findings provide some initial evidence of age acceleration among men and women with lower NGS and loss of strength over time. Future research is needed to understand the extent to which DNAm age mediates the association between grip strength and chronic disease, disability and mortality.